Strategies for Well-Being in New Work Spaces: A Case Study in a Post-Pandemic Context [Estrategias Para el Bienestar en Nuevos Espacios de Trabajo: Un Estudio de Caso en Un Contexto Pospandémico] - Araya-Leon, M (Elisava Barcelona School of Design and Engineering, 2022)
People’s priorities have changed as a result of the COVID-19 pandemic, with impacts on architectural experiences and work spaces in particular as teleworking and technology have become increasingly relevant in this new reality. Moreover, there is increased interest in the impact that spaces have on health, productivity and well-being as variables such as lighting, acoustics, biophilia, shape, composition, size and more influence perception and emotional, cognitive and behavioural states. Evidence-based design makes it possible to scientifically understand information about the situations present before and after an action, providing a more holistic view of the phenomenon through parameterisation and producing an impact on decision-making as seen in the case of this study. This article presents a case study developed through a mixed methodology that combines theoretical research methods to gain scientific knowledge on the topic and trends in the sector, as well as empirical methods to study the specific context of the corporate headquarters at Tous in Manresa. As to the theoretical side of the paper, we have conducted a literature review in the WOS (Web of Science) database, complemented by two trend reports on the future of workspaces. Regarding the empirical study, we programmed three different sources to compile data from workers at different times, spaces and platforms. In parallel, we measured the parameters of the built environment in different locations over two work days. Among the results, the following stand out: the universe of relationships, evidenced by cross-disciplinary departments such as HR (human resources) and IT (computer technology), as well as the relationship between the Product, Sales, R&D and After-Sales departments; the status of employees, with neutral or positive values in cognitive states, and of the environment, space lacking colour and with little brightness and neutral in terms of light colour, atmosphere and ventilation; the detection of the positive aspects to improve and to incorporate; and the measurement of the physical parameters of the environment, high noise level, CO2 within the comfort range, high temperatures and over illuminated or poorly lit spaces, and their perception. Finally, we propose scientific evidence and trends arising from the relationship between objective and subjective data as a result of design strategies focused on people’s well-being. These results are taken as the basis for making the changes implemented within a space. © 2022, Elisava Barcelona School of Design and Engineering. All rights reserved.